Long-acting anti-corrosion coating process for nodular cast iron fan hub and application

By employing a multi-layer gradient coating system and specialized treatment, the problems of insufficient coating adhesion and accelerated corrosion in the wind turbine hub coating process have been solved, achieving high reliability and long-term protection for the wind turbine hub.

CN120961405APending Publication Date: 2025-11-18RIYUE HEAVY IND (GANSU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511408164.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-29
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

Existing anti-corrosion coating processes for wind turbine hubs neglect the differences between the hub and the tower in terms of material, structure, stress state, and service environment, resulting in problems such as insufficient coating adhesion, uneven film thickness, easy brittle cracking, and accelerated corrosion.

Method used

The design employs a multi-layer gradient coating system, combined with coating processes tailored to the characteristics of ductile iron substrates, including workpiece cleaning, sandblasting for rust removal, and thermal spraying. It utilizes an epoxy zinc-rich primer containing zinc powder and silane coupling agent, an acrylic polyurethane topcoat with mica iron oxide, and a polyurethane-modified epoxy resin intermediate coat. Special treatments are applied to complex structures to ensure the adhesion and protective performance of the coating in harsh environments.

Benefits of technology

It significantly improves the adhesion, shielding and fatigue resistance of the coating on complex structures, realizes high reliability and maintenance-free operation of the wind turbine hub throughout its entire life cycle, and solves the corrosion problem of the hub.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of corrosion protection of key parts of wind power generation equipment, in particular to a long-acting anti-corrosion coating process for a nodular cast iron fan hub and application of the long-acting anti-corrosion coating process. Through multi-stage cleaning and soluble salt control, special sand blasting treatment for a complex cavity and design of a composite coating system containing specific components of primer, elastic intermediate paint and shielding finish paint, the adhesive force, fatigue resistance and long-term protection performance of the coating under a dynamic load are remarkably improved by combining edge pre-coating and thermal spraying with accurate parameters, and the service life of the coating is prolonged. And high-reliability protection of the fan hub in the whole life cycle is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of corrosion protection for key components of wind power generation equipment, specifically a long-lasting anti-corrosion coating process and application for ductile iron wind turbine hubs. Background Technology

[0002] As a crucial component of clean energy, the long-term reliability and service life of wind power equipment are of paramount importance. The wind turbine hub, as the core load-bearing component of the transmission system, transmits the enormous torque of the blades to the generator, and its operating condition directly affects the stability and safety of the entire machine. Located hundreds of meters in the air, the hub is subjected to extreme alternating loads and harsh environmental corrosion year-round. Early failure of its anti-corrosion coating will trigger severe substrate corrosion, leading not only to high downtime maintenance costs but also potentially catastrophic structural damage.

[0003] Currently, the anti-corrosion coating system in the wind power equipment manufacturing industry is relatively mature. However, for the special component of the wheel hub, there is a common technical misconception in the industry: simply applying the coating process and coating system of wind turbine towers to the wheel hub. The starting point for this approach is to simplify the supply chain and construction management, but it actually ignores the fundamental differences between the wheel hub and the tower in terms of materials, structure, stress conditions and service environment. Existing technologies for treating wind turbine hubs have the following inherent defects and shortcomings: First, regarding the substrate, the low-carbon steel (such as Q355) used in the tower is of uniform quality, while the hub is made of EN-GJS-400-18LT ductile iron. Its graphite phase acts as the cathode of a corrosion micro-cell, requiring significantly higher shielding and adhesion from the coating compared to the tower. Second, structurally, the tower's regular shape facilitates automated construction, while the hub has numerous irregular curved surfaces, deep holes, and cavities, making manual construction prone to defects such as missed coatings and uneven film thickness. Third, in terms of the mechanical environment, the tower bears static and low-frequency loads, while the hub bears high-frequency alternating stress and vibration, requiring the coating to possess higher flexibility, impact resistance, and fatigue resistance; otherwise, it is prone to brittle cracking. Fourth, regarding the internal environment, the tower has better ventilation, while the hub's enclosed cavity easily accumulates condensate, creating a highly humid, oxygen-deficient, and chloride-rich corrosive environment (pH can be below 3.5), exacerbating undercoat corrosion and paint film blistering.

[0004] Therefore, developing a dedicated long-lasting anti-corrosion coating process for ductile iron wind turbine hubs is of great significance for ensuring the safe and stable operation of wind turbine generator sets and reducing the total life cycle cost. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention proposes a long-term anti-corrosion process for wind turbine hub coating based on composite coating. This invention, through a multi-layer gradient coating system design combined with a coating process tailored to the characteristics of ductile iron substrates, significantly improves the coating's adhesion, shielding properties, fatigue resistance, and long-term protective performance in harsh environments on complex structures. This provides an innovative solution for achieving high reliability and maintenance-free operation of wind turbine hubs throughout their entire lifespan.

[0006] The first objective of this invention is achieved through the following technical solution:

[0007] A long-lasting anti-corrosion coating process for ductile iron fan hubs, the process including the steps of workpiece cleaning, sandblasting for rust removal, thermal spraying, and coating application.

[0008] Preferably, the coating system used in the coating application includes a primer, a topcoat, and an intermediate coat.

[0009] More preferably, the primer is an epoxy zinc-rich primer containing zinc powder and 1-3 wt% silane coupling agent.

[0010] More preferably, the zinc powder content in the primer is ≥85wt%, and the zinc powder particle size is 5-15μm.

[0011] More preferably, the silane coupling agent in the primer is any one or more of epoxy silanes, amino silanes, and methacryloxy silanes.

[0012] In a further preferred embodiment, the silane coupling agent in the primer is an aminosilane.

[0013] More preferably, the topcoat is an acrylic polyurethane topcoat containing mica iron oxide.

[0014] More preferably, the volume fraction of mica iron oxide in the topcoat is 20-25%.

[0015] More preferably, the intermediate paint is a polyurethane-modified epoxy resin intermediate paint, and its elastic modulus after curing is 2-4 GPa.

[0016] More preferably, the dry film thickness of the primer is 70-80 μm.

[0017] More preferably, the dry film thickness of the topcoat is 110-120 μm.

[0018] More preferably, the thickness of the intermediate paint dry film is 50-60 μm.

[0019] More preferably, the total dry film thickness of the coating system is 230-260 μm.

[0020] Preferably, the workpiece cleaning step includes:

[0021] 1) Pre-cleaning: Use a medium-high pressure water gun with a pressure of 10-20MPa to thoroughly rinse the wheel hub, initially removing loosely attached mud, sand, dust and other contaminants.

[0022] 2) Fine cleaning: For heavy contaminants such as oil and grease, use a handheld spray gun to spray alkaline cleaning agent. After a reaction time of 5-10 minutes, use a nylon brush, scouring pad or electric cleaning brush for manual scrubbing. Pay special attention to mechanical cleaning of areas that are prone to dirt accumulation, such as welds, corners and holes.

[0023] 3) Rinsing: Use a high-pressure fresh water gun with a pressure of 15-25MPa to rinse thoroughly until there is no cleaning agent residue, ensuring that the surface water film is continuous and unbroken.

[0024] 4) Soluble salt control: After rinsing, the surface rinse water is sampled and tested using a conductivity meter according to ISO 8502-6 or ISO 8502-9 standards to ensure that the soluble salt content is below 20 mg / m³. 2 This step is one of the keys to achieving long-term corrosion protection.

[0025] 5) Drying: Move the workpiece to a well-ventilated workstation for natural drying, or use a high-power industrial blower equipped with an oil-water separator to assist in drying, ensuring that there are no visible water marks on the surface before coating and that the humidity meets the standard requirements.

[0026] Preferably, the sandblasting rust removal includes sandblasting treatment of conventional surfaces, as well as specialized sandblasting treatment of cavities and holes.

[0027] Preferably, the sandblasting rust removal step is equipped with a laser scanner to monitor the surface roughness in real time, and uses a frequency-controlled sandblasting device to ensure cleanliness.

[0028] More preferably, the abrasive used for the sandblasting treatment of the conventional surface is high-carbon cast steel angular sand or a mixture of steel sand and steel shot.

[0029] More preferably, the high-carbon cast steel angular sand has a specification of G18 to G25.

[0030] More preferably, the mass ratio of steel grit to steel shot in the mixed abrasive is 2-3:1.

[0031] More preferably, after the conventional surface is sandblasted, the cleanliness of all surfaces to be coated reaches ISO8501-1Sa2.5 level, and the surface roughness is controlled within Rz40-75μm.

[0032] More preferably, the specialized sandblasting treatment for the cavities and holes involves using specialized tools to perform specialized sandblasting cleaning on the complex internal structure inside the wheel hub.

[0033] More preferably, the special sandblasting treatment for the cavities and holes uses high-carbon cast steel angular abrasive with specifications G25 to G40.

[0034] More preferably, the special tool includes, but is not limited to, any one or more combinations of an extendable and multi-angle guided sandblasting assembly, an internal inspection device, a manual finishing tool, and a residue removal system.

[0035] More preferably, the working air pressure of the sandblasting component is 0.5-0.7 MPa.

[0036] More preferably, the specialized sandblasting treatment includes the following steps:

[0037] 1) Preliminary investigation and rough cleaning stage: Use a long-handled reflector and a high-intensity flashlight to visually inspect the internal structure of the wheel hub (such as internal cavities, blind holes, holes, etc.), assess the degree of pollution and structural characteristics, and determine the key treatment areas.

[0038] 2) Main body sandblasting and rust removal stage: Use a long-handled spray gun to penetrate deep into the cavity and holes, and manually control the spraying angle and moving speed to uniformly sandblast the internal wall surface to remove oxide scale, rust and old coating.

[0039] 3) Local fine treatment and dead corner cleaning stage: For narrow areas, corners and welds that cannot be covered by the spray gun, use an angle grinder with fiber sanding disc or wire disc for local fine grinding.

[0040] 4) Stubborn residue treatment and surface finishing stage: For stubborn spot rust or adhesions remaining after mechanical treatment, use manual tools such as scrapers, pointed hammers, and wire brushes to scrape, knock or brush them off.

[0041] 5) Cleaning and Acceptance Stage: Use an air blower and vacuum cleaner to remove residual abrasive dust and debris from the interior. Finally, wipe the surface with a cleaning cloth and verify the cleanliness by visual inspection or by testing with an oil-free white cloth.

[0042] More preferably, the complex internal structure inside the hub is a hole structure on the hub, including but not limited to cavities, ventilation holes, bolt holes and blind bolt holes.

[0043] More preferably, after the cavity and hole treatment step, the cleanliness of all surfaces to be coated reaches ISO 8501-1Sa2.5 level.

[0044] More preferably, after the cavity and hole treatment step, the cleanliness of all surfaces to be coated reaches ISO 8501-1Sa3 level.

[0045] More preferably, after the cavity and hole treatment step, the roughness of all surfaces to be coated reaches Rz70-100μm.

[0046] Preferably, the thermal spraying step is as follows: using an arc spraying device, under process parameters of voltage 25-35V, current 200-300A, spraying distance 150-200mm, and spray gun moving speed 0.2-0.6m / s, a zinc or zinc-aluminum alloy layer is sprayed on the flange mating surface and key machined surfaces of the wheel hub to form a coating with a thickness of 150±30μm.

[0047] More preferably, the voltage of the arc spraying equipment is 28-32V.

[0048] More preferably, the spray gun moves at a speed of 0.3-0.5 m / s.

[0049] Preferably, in the coating process, when spraying the primer, intermediate coat and topcoat, the edges and corners of the wheel hub are pre-coated before the overall coating is applied.

[0050] Preferably, the coating application process is carried out in an environment with a temperature of 25±5℃ and a relative humidity of ≤75%, specifically including:

[0051] 1) Interval between primer coating and overcoating: After spraying the epoxy zinc-rich primer, control the overcoating interval to be 4-24 hours, preferably 8-12 hours, and then apply the polyurethane modified epoxy resin intermediate paint.

[0052] 2) Intermediate paint application: The intermediate paint is applied in multiple coats, with at least two coats applied to the designed total thickness. The recoating interval between each coat is controlled to be 30 to 90 minutes, preferably 50 to 70 minutes.

[0053] 3) Topcoat application and recoating interval: After the intermediate paint is applied, the recoating interval is controlled to be 16-24 hours, preferably 18-22 hours, before applying the acrylic polyurethane topcoat;

[0054] 4) Complete curing period: After all coating work is completed, the workpiece needs to be left to cure in the standard environment for at least 24 hours, preferably 48-72 hours, until the coating is completely cured and reaches the final performance index.

[0055] More preferably, the primer is applied at intervals of more than 24 hours, and the surface is lightly sandblasted (ISO8501-1Sa1 grade) before the intermediate coat is applied.

[0056] More preferably, the zinc powder content of the primer is controlled at 85wt%-90wt%.

[0057] More preferably, in the multi-coat process, the thickness difference between each coat is controlled to be ≤10μm.

[0058] More preferably, the intermediate paint coating interval exceeds 24 hours, and the surface is roughened before the topcoat is applied.

[0059] More preferably, the degree of curing of the intermediate coat should be ≥90% before the topcoat is applied.

[0060] Preferably, the final performance index of the coating application is a coating hardness ≥2H.

[0061] This technical solution, through precise design and system coordination at each stage, constructs a collaborative protection system specifically designed for the unique requirements of ductile iron wind turbine hubs.

[0062] Firstly, based on the characteristic that ductile iron materials are prone to micropores and casting defects on their surface, by including materials with a soluble salt content of less than 20 mg / m³... 2 The multi-stage cleaning process, including [specific steps], eliminates the potential for corrosive media to accumulate at defects from the source.

[0063] Secondly, considering the complex cavities and bolt holes of the wheel hub, which are difficult to handle with traditional processes, a special tool is used to achieve a cleanliness level of ISO 8501-1Sa2.5 and a roughness of Rz70-100μm. This not only cleans the surface macroscopically, but also provides a substrate with the best anchoring morphology for the coating microscopically.

[0064] To address the challenge of coating thinning in stress-concentrated areas such as wheel hub edges and corners, a dual protection approach combining pre-coating and a 150±30μm thermally sprayed zinc layer significantly enhances the protective capabilities of these vulnerable areas. The entire system, through multi-mechanism synergy, significantly improves coating adhesion, fatigue resistance, and long-term protective reliability under complex alternating stress environments.

[0065] In terms of coating system design, this solution features an innovative approach tailored to the specific working conditions of wheel hubs: A composite filler of 1-3 wt% silane coupling agent and 5-15 μm micron-sized zinc powder is added to the primer. Through a combination of chemical bonding and mechanical anchoring, the adhesion between the coating and the substrate (≥6 MPa) and its resistance to fretting wear are significantly improved. Instead of the conventional intermediate coat, flaky mica iron oxide (20-25 vol%) is placed in the topcoat. This not only allows the filler to fully utilize its physical shielding function but, more importantly, avoids an increase in the elastic modulus of the intermediate coat due to the addition of filler. The intermediate coat uses polyurethane-modified epoxy resin, with its modulus precisely controlled at 2-4 GPa to match the ductile iron substrate. This design enables it to absorb loads through elastic deformation, reducing the substrate stress amplitude by up to 30%, thereby effectively inhibiting stress corrosion crack propagation. Therefore, the functional separation of topcoat and intermediate coat achieves synergistic optimization of protective and mechanical properties; by special sandblasting and coating of the hole structure on the wheel hub, it is ensured that all edges, corners, welds and inner walls of holes can obtain a uniform, continuous coating with the designed thickness, thus achieving high stability control of the quality of complex workpieces.

[0066] The second objective of this invention is achieved through the following technical solution:

[0067] The application of the above-mentioned long-lasting anti-corrosion coating process in the coating protection of wind turbine hubs.

[0068] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0069] 1. The composite coating system design of this invention provides a comprehensive solution for the special working conditions of wheel hubs. The primer uses an epoxy zinc-rich primer containing zinc powder (≥85%, particle size 5-15μm) and 1-3wt% silane coupling agent. Through the dual effects of chemical bonding and mechanical anchoring, it significantly improves the penetration and adhesion of the coating on the microporous surface of ductile iron. Placing mica iron oxide in the topcoat rather than the intermediate coat ensures the maximization of its physical shielding function and avoids the increase in modulus of the intermediate coat due to filler addition. This ensures that the key elastic modulus of 2-4GPa of the intermediate coat is maintained, achieving an optimal match between the protective and mechanical properties of the coating system. The entire system works synergistically to perfectly match the stress characteristics and protection requirements of the wheel hub.

[0070] 2. This process achieves refined control throughout the entire process through systematic multi-step treatment, especially for ductile iron materials and the complex structure of wheel hubs. Compared with the tower process, this process includes specialized treatment steps for cavities and holes. Specialized tools such as long-handled spray guns, angle grinders with discs, and hand tools are used to thoroughly treat the complex internal structure of the wheel hub, ensuring that all surfaces to be sprayed achieve a cleanliness level of ISO 8501-1Sa2.5 and a roughness of Rz70-100μm. This treatment effect far exceeds the surface treatment requirements of the tower process, completely solving the problem of corrosion dead zones caused by the complex structure of the wheel hub.

[0071] 3. During the painting process, it was specifically stipulated that the edges and corners of the wheel hub should be pre-coated before overall spraying. This targeted measure effectively ensured the coating thickness and uniformity in these high-stress concentration areas, prevented premature edge corrosion, and solved the problem of uneven coating coverage caused by the complex geometry of the wheel hub.

[0072] 4. By strictly controlling the soluble salt content on the workpiece surface to be below 20 mg / m³ 2 This eliminates the risk of under-film corrosion at its source. This extremely stringent standard far exceeds the conventional requirements for towers, ensuring the long-term reliability of the hub under harsh environments.

[0073] 5. Precise thermal spraying process parameters are used to form a zinc or zinc-aluminum alloy coating with a thickness of 150±30μm on the substrate surface. This precise control ensures the density, uniformity, and optimal bonding strength of the metal protective coating, providing stable and durable electrochemical protection for the wheel hub. Detailed Implementation

[0074] The following will provide a clear and complete description of the concept, specific structure, and technical effects of the present invention in conjunction with embodiments, so as to fully understand the purpose, solution, and effects of the present invention. It should be noted that, unless otherwise specified, the embodiments and features described in the embodiments of the present invention can be combined with each other.

[0075] Unless otherwise specified, all raw materials used in the following examples and comparative examples are commercially available products.

[0076] Epoxy zinc-rich primer: Jotun HDG;

[0077] Polyurethane modified epoxy resin intermediate varnish: Jotun Jotacote F60;

[0078] Acrylic polyurethane topcoat: Jotun Futura Classic.

[0079] Example 1

[0080] The preparation steps of the anti-corrosion coated ductile iron fan hub in Example 1 include:

[0081] Step 1) Cleaning the workpiece

[0082] The wheel hub was thoroughly rinsed using a medium-high pressure water gun at 15 MPa. Then, Henkel P3-ferroclean series cleaner was sprayed using a handheld spray gun, allowing for an 8-minute reaction time. Afterward, manual scrubbing was performed using a nylon brush and scouring pad, with particular attention paid to mechanical cleaning of welds, corners, and pores. A thorough rinsing was then performed using a high-pressure fresh water gun at 20 MPa until no cleaner residue remained. Following ISO 8502-9 standards, the surface rinse water was sampled and tested using a conductivity meter, revealing a soluble salt content of 15 mg / m³. 2 Use a high-powered industrial hair dryer equipped with an oil-water separator to assist in drying, ensuring that there are no visible water marks on the surface before coating.

[0083] Step 2) Sandblasting to remove rust

[0084] A frequency converter-controlled sandblasting system was used, employing high-carbon cast steel angular abrasive. After treatment, all conventional surfaces to be sprayed achieved a cleanliness level of ISO 8501-1Sa2.5 and a surface roughness of Rz75μm. Specialized sandblasting cleaning was performed on the cavities, ventilation holes, bolt holes, and blind bolt holes inside the wheel hub. Using a combination of long-handled spray guns, angle grinders, and hand tools, a series of steps were performed: inspection, main body sandblasting, fine treatment of hard-to-reach areas, and cleaning. After these steps, the cleanliness of all such surfaces achieved an ISO 8501-1Sa2.5 level and a roughness of Rz85μm.

[0085] Step 3) Thermal spraying

[0086] Using the SmartArc series of arc spraying equipment from Meike, under process parameters of 30V voltage, 250A current, 180mm spraying distance, and 0.4m / s spray gun moving speed, a zinc layer is sprayed on the flange mating surface and key machined surfaces to form a coating with a thickness of 155μm.

[0087] Step 4) Coating Application

[0088] Construction should be carried out in an environment with a temperature of 25℃ and a relative humidity of 65%.

[0089] The epoxy zinc-rich primer, containing 86 wt% zinc powder with a particle size D50 of 10 μm, is sprayed. The coating contains 1.5 wt% γ-aminopropyltriethoxysilane (KH-550), and the dry film thickness is controlled at 80 μm. During application, the edges and corners of the wheel hub are pre-coated before the overall coating. A 10-hour interval is maintained between coats before proceeding to the next step. The polyurethane-modified epoxy resin intermediate coat is then sprayed, with a cured film elastic modulus of 3.2 GPa. A two-coat process is used, applying two coats to a total dry film thickness of 50 μm. The recoating interval between each coat is 30 minutes under standard conditions (25°C, 65% RH), and the surface dryness is determined by a combination of the finger-touch method (non-sticky) and the solvent wiping method (no softening or damage to the film). The thickness difference between the two coats is controlled to ≤8 μm. Twenty hours after the intermediate coat is applied, an acrylic polyurethane topcoat with a mica-iron oxide mixture (22% by volume) is sprayed on, with a dry film thickness controlled at 70 μm. After all coating is completed, the workpiece is left to cure under standard conditions for 60 hours.

[0090] Example 2

[0091] In the preparation steps of the anti-corrosion coated ductile iron fan hub in Example 2, steps 1) to 2) are the same as in Example 1, and steps 3) to 4) are as follows:

[0092] Step 3) Using the SmartArc series of arc spraying equipment, under the process parameters of voltage 30V, current 250A, spraying distance 180mm, and spray gun moving speed 0.4m / s, a zinc layer is sprayed on the flange mating surface and key machined surfaces to form a coating with a thickness of 180μm.

[0093] Step 4) Construction is carried out in an environment with a temperature of 25℃ and a relative humidity of 65%: Spray an epoxy zinc-rich primer with a zinc powder content of 86%, a particle size D50 of 10μm, and containing 1.5wt% γ-aminopropyltriethoxysilane (KH-550). The dry film thickness is controlled at 90μm. During coating, pre-coat the edges and corners of the wheel hub before overall spraying. After coating, wait 10 hours before proceeding to the next step. Spray a polyurethane-modified epoxy resin intermediate coat, with a cured film elastic modulus of 3.5GPa. Use a multi-coat application method. The coating process involves two coats to a total dry film thickness of 60 μm. The recoating interval between each coat is 30 minutes under standard conditions (25℃, 65% RH), and the surface dryness is determined by a combination of finger touch and solvent wiping methods. The thickness difference between the two coats is controlled to be ≤8 μm. 20 hours after the intermediate coat is applied, an acrylic polyurethane topcoat mixed with mica iron oxide is sprayed, with a volume fraction of 22% mica iron oxide, and the dry film thickness is controlled to be 80 μm. After all coatings are completed, the workpiece is left to cure under standard conditions for 60 hours.

[0094] Comparative Example 1

[0095] In the preparation of the anti-corrosion coated ductile iron fan hub in Comparative Example 1, steps 2)-4) are the same as in Example 1, except that step 1) is:

[0096] Step 1) Thoroughly rinse the wheel hub using a medium-high pressure water gun at 15 MPa, then spray Henkel P3-ferroclean series cleaner using a handheld spray gun, allowing a 3-minute reaction time. Next, thoroughly rinse with a high-pressure fresh water gun at 20 MPa until no cleaner residue remains. Following ISO 8502-9 standard, sample the surface rinse water using a conductivity meter; the soluble salt content was measured to be 28 mg / m³. 2 .

[0097] Comparative Example 2

[0098] In the preparation of the anti-corrosion coated ductile iron fan hub in Comparative Example 2, steps 1), 3), and 4) are the same as in Example 1, and step 2) is:

[0099] Step 2) Use a frequency converter-controlled sandblasting equipment and select high-carbon cast steel angular abrasive to sandblast all surfaces of the workpiece. After treatment, the cleanliness of the smooth surface reaches ISO 8501-1Sa2.5 level, and the surface roughness is Rz75μm.

[0100] Comparative Example 3

[0101] In the preparation of the anti-corrosion coated ductile iron fan hub in Comparative Example 3, steps 1)-3) are the same as in Example 1, and step 4) is:

[0102] Step 4) Construction is carried out in an environment with a temperature of 25℃ and a relative humidity of 65%: Spray an epoxy primer (Jotunastic 87AL) containing mixed zinc powder, with a zinc powder content of 86% and an average particle size of 20μm, containing 1.5wt% γ-aminopropyltriethoxysilane (KH-550), and controlling the dry film thickness to 80μm; Pre-coat the edges and corners of the wheel hub before overall spraying; allow 10 hours between coats before proceeding to the next step; Spray a polyurethane-modified epoxy resin intermediate coat, with a cured film elastic modulus of 3.2GPa; Use a two-coat application process, spraying two coats to the total dry film thickness. The thickness is 50μm; the recoating interval between each spray is 30 minutes under standard environment (25℃, 65%RH), and the surface dryness is determined by a combination of finger touch method and solvent wiping method; the thickness difference between two paint films is controlled to be ≤8μm; 20 hours after the intermediate paint is applied, an acrylic polyurethane topcoat with mixed mica iron oxide is sprayed, with a volume fraction of 22% mica iron oxide and a dry film thickness controlled to be 70μm; after all coating is completed, the workpiece is left to cure under standard environment for 60 hours.

[0103] Comparative Example 4

[0104] In the preparation of the anti-corrosion coated ductile iron fan hub in Comparative Example 4, steps 1)-3) are the same as in Example 1, and step 4) is:

[0105] Step 4) Construction is carried out in an environment of 25℃ and 65% relative humidity: Spray an epoxy zinc-rich primer with a zinc powder content of 86%, a particle size D50 of 10μm, and containing 1.5wt% γ-aminopropyltriethoxysilane (KH-550). The dry film thickness is controlled at 80μm. During coating, pre-coat the edges and corners of the wheel hub before overall spraying. After coating, wait 10 hours before proceeding to the next step. Spray a polyurethane-modified epoxy resin intermediate coat containing mixed mica iron oxide, with a mica iron oxide volume fraction of 22%. The elastic modulus of the cured coating is 6.4 GPa; a two-coat process is adopted, with two coats sprayed to a total dry film thickness of 50 μm; the recoating interval between each coat is 30 minutes under standard conditions (25℃, 65% RH), and the surface dryness is determined by a combination of finger touch and solvent wiping methods; the thickness difference between the two coats is controlled to ≤8 μm; 20 hours after the intermediate coat is applied, an acrylic polyurethane topcoat is sprayed, with a dry film thickness controlled to 70 μm; after all coatings are completed, the workpiece is left to cure under standard conditions for 60 hours.

[0106] Comparative Example 5

[0107] In the preparation of the anti-corrosion coated ductile iron fan hub in Comparative Example 5, steps 1)-3) are the same as in Example 1, and step 4) is:

[0108] Step 4) Construction is carried out in an environment with a temperature of 25℃ and a relative humidity of 65%: Spray an epoxy zinc-rich primer with a zinc powder content of 86%, a particle size D50 of 10μm, and containing 1.5wt% γ-aminopropyltriethoxysilane (KH-550). The dry film thickness is controlled at 80μm. During coating, pre-coat the edges and corners of the wheel hub before overall spraying. After coating, wait 10 hours before proceeding to the next step. Spray a polyurethane-modified epoxy resin intermediate coat; the elastic modulus of the cured film is... The pressure is 3.2 Pa; a two-coat process is adopted, with two coats sprayed to a total dry film thickness of 50 μm; the recoating interval between each coat is 30 minutes under standard conditions (25℃, 65% RH), and the surface dryness is determined by a combination of finger touch and solvent wiping methods; the thickness difference between the two coats is controlled to be ≤8 μm; 20 hours after the intermediate coat is applied, an acrylic polyurethane topcoat is sprayed, with a dry film thickness controlled to be 70 μm; after all coating is completed, the workpiece is left to cure under standard conditions for 60 hours.

[0109] The anti-corrosion coated ductile iron fan hubs prepared in Examples 1-2 and Comparative Examples 1-5 were subjected to the following tests:

[0110] Neutral salt spray test (NSS): Conducted in accordance with ISO 9227 standard.

[0111] Adhesion (pull-off test): Performed in accordance with ISO 4624 standard.

[0112] Bending fatigue test: Apply ±1° deflection according to ASTM D6272 standard.

[0113] Impact resistance: According to ISO 6272 standard, the impact energy is 1 J·m.

[0114] Pencil hardness: Refer to ASTM D3363 standard.

[0115] Abrasion resistance: Based on ASTM D4060 standard, using CS-10 grinding wheels, grinding was performed at 1000 revolutions under a 1000g load.

[0116] The results are shown in Table 1 below:

[0117] Table 1. Test results of Examples 1-2 and Comparative Examples 1-5

[0118]

[0119] Example 1 demonstrates the superior overall performance achieved under the standard process parameters of this invention, with all test indicators significantly exceeding current industry standards. Example 2 further improves all performance indicators by moderately increasing the thickness of the key protective coating, particularly excelling in salt spray corrosion resistance and fatigue resistance. This indicates that the process of this invention has good scalability and can meet the requirements of future higher-power wind turbine hubs for longer design life and higher reliability. Together, the two examples constitute a complete solution from standard applications to high-performance requirements, and their comprehensive and superior performance reflects the synergistic protective effect brought about by complete and precise process design. The sharp decline in adhesion and salt spray resistance of Comparative Example 1 (high-salt surface) highlights the irreplaceable role of surface cleanliness as the cornerstone of long-term protection, proving that the strict surface treatment process in this invention is crucial for ensuring the service life of the coating. Comparative Example 2 (special treatment without cavities) exhibits extremely poor adhesion and early corrosion failure inside cavities, emphasizing the necessity of specialized sandblasting treatment for complex internal structures, proving that this dedicated process is indispensable for achieving all-round, no-dead-angle protection. The decreased shielding and adhesion of Comparative Example 3 (large-particle-size zinc powder) led to a deterioration in corrosion resistance, indicating that the particle size of zinc powder significantly affects the density and electrochemical protection efficiency of the primer coating, highlighting the precise control of key raw material parameters in this invention. Comparative Example 4 (MIO filler misalignment) showed significantly lower flexural fatigue resistance and adhesion than Example 1, indicating that this design weakens the dynamic mechanical properties and bonding strength of the coating system; simultaneously, its weather resistance was severely insufficient, proving that mica iron oxide cannot effectively perform its anti-aging function in the intermediate coat. This result underscores the necessity of precisely configuring fillers in the topcoat for simultaneously ensuring excellent mechanical properties and ultra-long-lasting weather resistance. The coating system of Comparative Example 5 (without MIO filler) showed comprehensive deterioration in corrosion resistance, mechanical strength, and weather resistance, confirming that mica iron oxide is an essential functional component for achieving the comprehensive protection objectives of this invention.

[0120] The specific embodiments described herein are merely illustrative of the spirit of the invention. Those skilled in the art to which this invention pertains may make various modifications or additions to the described specific embodiments or use similar methods to substitute them without departing from the spirit of the invention or exceeding the scope defined by the appended claims.

Claims

1. A long-lasting anti-corrosion coating process for ductile iron fan hubs, characterized in that, The process includes the steps of workpiece cleaning, sandblasting for rust removal, thermal spraying, and coating application; the coating system used in the coating application includes primer, topcoat, and intermediate coat; The primer is an epoxy zinc-rich primer containing zinc powder and 1-3 wt% silane coupling agent; The topcoat is an acrylic polyurethane topcoat containing mica iron oxide; The intermediate paint is a polyurethane-modified epoxy resin intermediate paint, and its elastic modulus after curing is 2-4 GPa.

2. The process according to claim 1, characterized in that, The zinc powder content in the primer is ≥85wt%, and the zinc powder particle size is 5-15μm.

3. The process according to claim 1, characterized in that, The volume fraction of mica iron oxide in the topcoat is 20-25%.

4. The process according to claim 1, characterized in that, The sandblasting rust removal includes sandblasting treatment of conventional surfaces, as well as specialized sandblasting treatment of cavities and holes.

5. The process according to claim 4, characterized in that, The specialized sandblasting treatment of the cavities and holes is performed using specialized tools, which include any one or more of the following: an extendable and multi-angle guided sandblasting assembly, an internal inspection device, a manual finishing tool, and a residue removal system.

6. The process according to claim 4, characterized in that, The specialized sandblasting treatment for the cavities and holes includes the following steps: 1) Preliminary investigation and rough cleaning stage: Use a long-handled reflector and a flashlight to visually inspect the internal structure of the wheel hub, assess the degree of contamination and structural characteristics, and determine the key areas for treatment; 2) Main body sandblasting and rust removal stage: Use a long-handled spray gun to penetrate deep into the cavity and hole, and manually control the spraying angle and moving speed to uniformly sandblast the internal wall surface to remove oxide scale, rust and old coatings. 3) Local fine treatment and dead corner cleaning stage: For narrow areas, corners and welds that cannot be covered by the spray gun, use an angle grinder with fiber sanding disc or steel wire disc for local fine grinding. 4) Stubborn residue treatment and surface finishing stage: For stubborn spot rust or adhesions remaining after mechanical treatment, use hand tools to scrape, knock or brush them off. 5) Cleaning and Acceptance Stage: Use an air blower and vacuum cleaner to remove residual abrasive dust and debris from the interior. Finally, wipe the surface with a cleaning cloth and verify the cleanliness by visual inspection or by testing with an oil-free white cloth.

7. The process according to claim 1, characterized in that, In the sandblasting and rust removal step, the sandblasting treatment of the conventional surface uses high-carbon cast steel angular sand with specifications of G18 to G25 or a mixed abrasive of steel sand and steel shot with a mass ratio of 2-3:

1. And / or, the special sandblasting treatment of the cavities and holes uses high-carbon cast steel angular abrasive with a specification of G25 to G40.

8. The process according to claim 1, characterized in that, The workpiece cleaning includes the following steps: 1) Pre-cleaning: Use a medium-high pressure water gun with a pressure of 10-20MPa to thoroughly rinse the wheel hub, initially removing contaminants such as mud and dust that are not strongly attached; 2) Fine cleaning: For heavy contaminants, use a handheld spray gun to spray alkaline cleaning agent, retain the reaction time for 5-10 minutes, and then use a nylon brush, scouring pad or electric cleaning brush for manual scrubbing. 3) Rinsing: Use a high-pressure fresh water gun with a pressure of 15-25MPa to rinse, ensuring that the surface water film is continuous and unbroken; 4) Soluble salt control: After rinsing, the surface rinse water is sampled and tested using a conductivity meter according to ISO 8502-6 or ISO 8502-9 standards to ensure that the soluble salt content is below 20 mg / m³. 2 .

9. The process according to claim 1, characterized in that, The thermal spraying step is as follows: using an arc spraying device, under process parameters of voltage 25-35V, current 200-300A, spraying distance 150-200mm, and spray gun moving speed 0.2-0.6m / s, a zinc or zinc-aluminum alloy layer is sprayed on the flange mating surface and key machined surfaces to form a coating with a thickness of 150±30μm.

10. The application of a long-lasting anti-corrosion coating process as described in any one of claims 1-9 in the coating protection of wind turbine hubs.